(untitled) (Diliman, Quezon City, Philippines, 2004)
The CBCRM Festival created a venue for practitioners and advocates to celebrate and reflect on the gains and challenges of the CBCRM movement, share these lessons with the larger public, and together look at how to take it forward.
Keywords: Coastal zone management,Social participation,Community organization,Phillippines coastal resources; Philippines,Philippines,Philippines